Through-The-Earth (TTE) communication systems : channel characterization and system evaluation - Peña Carreño, Josua Daniel (2020)
Tese (doutorado)—Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Elétrica, 2020.